2017
DOI: 10.1194/jlr.m071357
|View full text |Cite
|
Sign up to set email alerts
|

FoxO3 increases miR-34a to cause palmitate-induced cholangiocyte lipoapoptosis

Abstract: Nonalcoholic steatohepatitis (NASH) patients have elevated plasma saturated free fatty acid levels. These toxic fatty acids can induce liver cell death and our recent results demonstrated that the biliary epithelium may be susceptible to lipotoxicity. Here, we explored the molecular mechanisms of cholangiocyte lipoapoptosis in cell culture and in an animal model of NASH. Treatment of cholangiocytes with palmitate (PA) showed increased caspase 3/7 activity and increased levels of cleaved poly (ADP-ribose) polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 51 publications
(90 reference statements)
1
30
0
Order By: Relevance
“…Although the precise mechanism whereby obesity induces adipose miR-34a expression remains unknown, both our results and previous studies showed that TNF-α, a proinflammatory cytokine that is elevated at the very early stage of obesity, increases miR-34a expression (40,41). Furthermore, in line with our results, palmitate, a toxic lipid that is increased in obesity, has been reported to induce miR-34a expression through the activation of the transcription factor Foxo3 (42). Therefore, the increased miR-34a expression in obese adipose tissue might be attributed to the synergistic effects of various metabolic stress-induced signaling cascades.…”
Section: Discussionsupporting
confidence: 89%
“…Although the precise mechanism whereby obesity induces adipose miR-34a expression remains unknown, both our results and previous studies showed that TNF-α, a proinflammatory cytokine that is elevated at the very early stage of obesity, increases miR-34a expression (40,41). Furthermore, in line with our results, palmitate, a toxic lipid that is increased in obesity, has been reported to induce miR-34a expression through the activation of the transcription factor Foxo3 (42). Therefore, the increased miR-34a expression in obese adipose tissue might be attributed to the synergistic effects of various metabolic stress-induced signaling cascades.…”
Section: Discussionsupporting
confidence: 89%
“…Cholestatic presentation of NASH has been suggested to develop in a subset of patients [ 119 ] and FFAs induce apoptosis not only in hepatocytes but also in cholangiocytes. Indeed, cholangiocyte lipoapoptosis has been shown to occur in high fat-high sucrose-fed mice [ 117 , 120 ]. Natarajan et al recently found that FFAs induced apoptosis of cholangiocytes through forkhead box O3 (Foxo3)-mediated miR-34a (Fig.…”
Section: Epigenetic Factors and Hepatocyte Lipotoxicity: Novel Targetmentioning
confidence: 99%
“…In NASH, the primary sources of Hh ligands are the injured hepatic epithelial cells, particularly lipotoxic hepatocytes (Rangwala et al, 2011; Guy et al, 2012) and reactive cholangiocytes (Natarajan et al, 2014; Natarajan et al, 2017). In hepatocytes, fatty acid toxicity provokes ER and apoptotic-stress, resulting in disruption of the cytoskeleton and swelling (a.k.a., ballooning).…”
Section: Physiology Of the Hedgehog Pathway In The Livermentioning
confidence: 99%